Analysis of determinant factors affecting retail business customer loyalty - Haris, Abdul; Rahman, Abdul; Yusriadi, Yusriadi; Farida, Umi (Linguistics and Culture Review, 2021)
Demographic development is the first field that influences the growth of retail stores. The rising population allows all goods and services to increase. To establish customer loyalty, the company must try to try to offer the highest quality in any product or service it must create a positive sense of quality in the minds of its customers. This research is a descriptive research type, trying to explain and describe each variable’s conditions in detail and see the relationship or relationship between these variables. In the context of this study, the independent variables are Service Quality (X1), Relationship Marketing (X2), and Customer Satisfaction (Y), while the dependent variable is Customer Loyalty (Z). Quantitative data were analyzed using descriptive analysis and Structural Equation Modelling (SEM) analysis. Partially service quality has a significant influence on customer satisfaction in modern stores. In the sense that the quality of service provided by modern store management in Makassar City can contribute positively to customer satisfaction with the five dimensions of Tangible, Reliability, Empathy, Assurance, and Responsiveness. Direct service quality significantly influences customer loyalty, and indirect service quality has a significant effect on customer loyalty (LP) through customer satisfaction at modern stores in Makassar City.